Genotyping of Borrelia from formalin‐fixed paraffin‐embedded skin biopsies of cutaneous borreliosis and tick bite reactions by assays targeting the intergenic spacer region, ospA and ospC genes. (27th August 2014) - Brandt, F.C.; Ertas, B.; Falk, T.M.; Metze, D.; Böer‐Auer, A.
Summary: Background: Lyme borreliosis has a broad spectrum of clinical presentations involving the skin, joints and nervous system. The variable manifestations have been attributed to different Borrelia genospecies but genotyping required culture or fresh tissue. However, in dermatology practice, formalin‐fixed paraffin‐embedded biopsies are used for dermatopathological examination. Polymerase chain reaction (PCR) for Borrelia burgdorferi sensu latu has been established on such specimens, but studies attempting genotyping of subspecies or strains are lacking. Objectives: To adapt PCR assays for genotyping of Borrelia using paraffin‐embedded biopsies, to identify Borrelia genospecies and to compare clinicopathological features of different genospecies. Methods: Eighty‐two paraffin‐embedded biopsies from 68 patients, with erythema migrans, acrodermatitis chronica atrophicans, lymphocytoma cutis or tick bite reactions, were studied with assays targeting the intergenic spacer (IGS), ospA and ospC, followed by sequencing and phylogenetic analysis. Clinicopathological data were analysed comparing different Borrelia genospecies. Results: Genotyping by IGS, ospA and ospC was successful in 85% of patients (91% B. afzelii, 7% B. garinii, 2% B. bavariensis ). ospA serotyping identified type 2 (90%), type 3 (8%) and type 4 (2%). ospC ‐PCR was positive in 40% of the patients revealing 12 different groups, noninvasive forms being seen only in tick bite reactions and erythema migrans. No major clinicopathological differences could be identified between the genospecies, but neural inflammation and arthralgia were seen more often in lesions caused by invasive ospC strains. Conclusions: Genotyping of Borrelia can be easily implemented in a routine dermatopathology setting, especially as a fast method to confirm early cutaneous borreliosis. Genotyping could also enable earlier treatment of patients infected with invasive strains. Abstract : What's already known about this topic? Different Borrelia genospecies are considered to be responsible for the protean manifestations of Lyme borreliosis. Polymerase chain reaction (PCR)‐based genotyping requires fresh tissue or culture, and culture is technically difficult and time consuming. What does this study add? Conventional PCR assays for the intergenic spacer, ospA and ospC successfully identified Borrelia genospecies in paraffin‐embedded biopsies from a routine dermatopathology laboratory. This approach may serve as rapid confirmation of early borreliosis and enable identification of invasive ospC strains with possible therapeutic implications.